Treadmill Exercise Impact on Brain Electrophysiological and Glial Immunoreactivity in Cuprizone-Treated Rats - Cássia Borges Lima-de-Castro; Noranege Epifânio Accioly; Geórgia de Sousa Ferreira Soares; Catarina Nicácio dos-Santos; Sonia Carolina Guerrero Prieto; Rubem Carlos Araujo Guedes (Brain Sciences)
Background/Objectives: Demyelination occurs to a variable extent in various neurological diseases, such as multiple sclerosis. Physical exercise benefits central neural functions that depend on the brain’s electrophysiological and glial activity. It is unclear whether both factors—i.e., demyelination and exercise—interact in the brain. We aimed to investigate if this interaction occurs during brain development. Methods: Developing rats were subjected to a cuprizone-induced demyelination. Part of these rats were treadmill-exercised for five weeks. After this period, some demyelinated animals were allowed to remyelinate by receiving a similar diet, without cuprizone, for six weeks. The exercised groups were compared with the corresponding sedentary groups. All groups were evaluated electrophysiologically (cortical spreading depression features), and their brains were processed for immunohistochemical labeling with four specific glial antibodies (anti-APC, MBP, GFAP, and Iba1). Results: Compared with the corresponding controls, cuprizone demyelination and treadmill exercise accelerated and decelerated CSD propagation. Cuprizone reduced APC, MBP, and GFAP immunolabeling and increased Iba1 immunostaining. Remyelination reverted the cuprizone effects. Exercise counteracted the cuprizone-induced changes in GFAP- and Iba1-containing cells but not in MBP- and APC-containing ones. Conclusions: Our data confirmed the effectiveness of the cuprizone demyelination paradigm. They evidenced the potential neuroprotective effect of regular physical exercise, suggesting that this non-pharmacological intervention could benefit patients with central demyelination-dependent diseases.